POLEMIK EPISTEMOLOGI PANCASILA DAN DEMOKRASI YANG KONSTRUKTIF BESERTA IMPLEMENTASINYA - Agustinus Edward Tasma; Heru Santoso (Humanika, Kajian Ilmiah Mata Kuliah Umum, 2006)
As cristalization values of Indonesion basics, Pancasila has reflections of our self of Nations. Pancasila has representation of everything differents in Nusantara Islands. With Pancasila it can be used on missions for our governents. In Indonesian conditions has wached essential of Pancasila as phylosophies groundlach and we have concern of phylosophy  as way of live by differents in Indonesian governent.